Prevalance and correlates of permanent tooth mortality and its impact on wellbeing - Perera, A.M.L.R (My University, 2009)
The study was conducted in two phases phase I and phase II. The sample for phase I consisted of a total of 1380 individuals who were aged 20 and above selected from 60 clusters in the Colombo district. Data were collected by means of an interviewer administered questionnaire, clinical oral examination and physical examination. The number of missing teeth and adjusted missing teeth, associations between tooth loss and sociodemographic and behavioral variables, minimum number of teeth needed for satisfactory oral health related quality of life and the effect of tooth loss on the nutritional status were assessed in this phase of the study. Phase II: The sample included of 480 individuals who were 20 years and above attending dental clinics for a dental extraction who received an appointment for a dental extraction and/or who eventually ended' up with dental extraction. This phase assessed the reasons for tooth extraction and factors leading to the decision to extract teeth. The minimum number of teeth needed for satisfactory oral health related quality of life for the two age groups 40-59 and 60 year were 26-27 and 21-22 teeth respectively. BMI and BMA were significantly associated (pO.O I) with missing teeth. Prevalence of malnutrition was 19.3 percent and 29.8 percent when BMl and BMA were considered respectively.